2023
DOI: 10.2174/1574892817666220316152201
|View full text |Cite
|
Sign up to set email alerts
|

LINC00936/microRNA-221-3p Regulates Tumor Progression in Ovarian Cancer by Interacting with LAMA3

Abstract: Background: Ovarian cancer remains a leading cause of mortality in women. It is known that long non-coding RNA (lncRNA) controls various biological processes and pathogenesis of many diseases, including cancers. This study aimed to determine whether LINC00936 and microRNA-221-3p (miR-221-3p) influence the laminin alpha 3 chain gene (LAMA3) in the development of ovarian cancer. Methods: The expressions of LINC00936, miR-221-3p, and LAMA3 in ovarian cancer and adjacent tissues were assessed. Furthermore, ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Recent studies have implicated elevated LAMA3 expression in various types of tumors, where it appears to promote cell proliferation, apoptosis, and tumor progression by modulating signal transduction pathways. 7 , 8 , 9 Zboralski et al demonstrated the simultaneous functional inactivation of the tumor suppressor mothers against decapentaplegic homolog 4 (SMAD4) and invasive growth of tumors in rectal and pancreatic cancers. Laminin 332 (LM-332) is the target of SMAD4, a positive transcriptional regulator that promotes the transcription of LAMA3, LAMB3, and LAMC2 genes encoding LM-332.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have implicated elevated LAMA3 expression in various types of tumors, where it appears to promote cell proliferation, apoptosis, and tumor progression by modulating signal transduction pathways. 7 , 8 , 9 Zboralski et al demonstrated the simultaneous functional inactivation of the tumor suppressor mothers against decapentaplegic homolog 4 (SMAD4) and invasive growth of tumors in rectal and pancreatic cancers. Laminin 332 (LM-332) is the target of SMAD4, a positive transcriptional regulator that promotes the transcription of LAMA3, LAMB3, and LAMC2 genes encoding LM-332.…”
Section: Discussionmentioning
confidence: 99%
“…Shu et al demonstrated that the overexpression of LINC00936 hindered ovarian cancer progression by competitively binding to miR-221-3p and modulating LAMA3 expression. 7 Moreover, Xu et al reported that LINC00628 could obstruct cell proliferation, invasion, migration, and apoptosis while reducing drug resistance in lung adenocarcinoma cells by downregulating the methylation of the LAMA3 promoter 8 . Kinoshita et al demonstrated that miRNA-218 modulated the focal adhesion pathway, thereby impeding tumor cell invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LAMA3 gene can encode the α3 chain of laminin-5, which is an important cell membrane component and regulates cell adhesion and migration ( Zhang et al, 2018 ; Xu et al, 2019 ). Studies indicated that LAMA3 is a promising target for cancer therapy since it may accelerate the growth and invasion of tumour cells ( Xu et al, 2019 ; Shu et al, 2023 ). This agrees with our research suggesting that LAMA3 might be a useful treatment target for PC.…”
Section: Discussionmentioning
confidence: 99%
“…17 ATP2B1-AS1/miR-221-3p/LAMA3 axis modulates the progression of ovarian cancer. 18 However, the role of ATP2B1-AS1 in sepsis is still unclear.…”
Section: Introductionmentioning
confidence: 99%